Sotsialno-psikhologicheskie kharakteristiki razygryvayushchego igroka v basketbole - Khutsinski, T. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
About the role and necessary characteristics of the "fiddling player", e.g. the most important player in a team who has different tasks at different positions in a match (he plays not only as an attacker or a defensive player).